2022
DOI: 10.1039/d2tc02268k
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency luminescent organic–inorganic hybrid manganese(ii) halides applied to X-ray imaging

Abstract: Organic-inorganic hybrid manganese halides with low cost, facile synthesis, and high-efficient luminescence have emerged as the novel candidate materials for X-ray detection and imaging. In this work, a series of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…The weight loss from 580 to 983 K is about 74% for 1 , whereas that from 573 to 750 K is about 71.2% for 2 , which is attributed to the loss of organic cations and chloride atoms (calculation: 68.6% for both 1 and 2 ). The decomposition temperatures of 1 and 2 are comparable to those of other OIMHs. , DSC measurements revealed that the exothermic peaks appeared at 499 and 512 K for 1 and 2 , respectively, with the increase of temperature (Figure S3c,d), indicating that they have a high phase transition temperature.…”
Section: Resultssupporting
confidence: 59%
“…The weight loss from 580 to 983 K is about 74% for 1 , whereas that from 573 to 750 K is about 71.2% for 2 , which is attributed to the loss of organic cations and chloride atoms (calculation: 68.6% for both 1 and 2 ). The decomposition temperatures of 1 and 2 are comparable to those of other OIMHs. , DSC measurements revealed that the exothermic peaks appeared at 499 and 512 K for 1 and 2 , respectively, with the increase of temperature (Figure S3c,d), indicating that they have a high phase transition temperature.…”
Section: Resultssupporting
confidence: 59%
“…It is related to the de-excitation of Mn 2+ 4 T 1 ( 4 G) to 6 76%, which is higher than that of other reported 0D Mn(II)-based hybrid scintillators, such as 59.4% for (C 5 H 6 N) 2 MnBr 4 [42] and 60.3% for TEA 2 MnI 4 . [46] Previously reported red-emitting Mn(II) halides with Mn-Mn distance <5 Å, such as CsMnBr 3 [32] and C 4 H 10 NMnBr 3 , [47] have a strong concentration quenching effect, resulting in a low PLQY with a nanosecond decay. In this case, the large Mn-Mn distance of ≈8.551 Å between adjacent trimeric [Mn 3 Cl 12 ] 6− prevents energy migration due to effective separation of Mn 2+ luminescence center, reducing the nonradiative energy dissipation, thereby leading to a long decay time of 1.7 ms and a high PLQY of 75.7%.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the recent developed Mn(II)‐based hybrids are tetrahedrally green emission, such as (C 38 H 34 P 2 )MnBr 4 , [ 27 ] (ETP) 2 MnBr 4 , [ 31 ] and (C 22 H 22 O 2 P) 2 MnBr 4 . [ 32 ] Compared to the green‐emitting Mn‐based halides, the octahedrally coordinated red‐emitting counterparts possessing larger Stokes shift and higher PLQY are rarely studied. For instance, Yang Yang et al reported a one‐dimensional (1D) C 4 H 12 NMnCl 3 with octahedrally coordinated field showed higher PLQY (91.8% vs 85.1%) and higher steady‐state light yields (50 500 photons MeV −1 vs 24 400 photons MeV −1 ) than tetrahedrally coordinated 0D (C 8 H 20 N) 2 MnBr 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantages of eco-friendliness, low cost and high luminescence quantum efficiency, manganese(II) halides can be used for promising and efficient luminescent materials. [23][24][25][26] Their luminescence mechanism comes from the d orbital electron transition in the crystal field. [27][28][29] At present, manganesebased hybrid halides are widely used in light-emitting diodes, solar cells, photoelectric detection and other fields.…”
Section: Introductionmentioning
confidence: 99%